دعم ثقافة الجودة في مؤسسات التعليم العالي: دراسة حالة جامعة بنغازي - بن إسماعيل عياد طاهر (Scientific Journal of University of Benghazi, 2020)
It is widely recognized the importance of education in general and of higher education for the future of a nation. Quality culture represents a very important factor for any type of organization, be it school, university, not-for-profit groups, government agencies or business entities. This study aims to identify the role of quality culture in improving academic, managerial and societal performance of University of Benghazi. To address this problem and achieve the aim of the study, we adopted the qualitative approach with a qualitative analysis of data from interviews conducted with managers of quality assurance offices in ten colleges. In the end, the study concluded a set of recommendations that supports University of Benghazi in finding ways how to enhance quality culture in teaching and learning.